Assessing Long-Run Price Convergence in Retailing - Fernando Borraz; Leandro Zipitría (Global Labor Organization (GLO), 2024)
We assess price dispersion in retail markets and its sources over time. Using a product-detailed price database, we document a consistent divergence of prices over time in retail markets in Uruguay: price dispersion increased by 3.1% in fifteen years. Next, we analyze microeconomic and macroeconomic factors that correlate with price dispersion. We differentiate the effect in the short-run-i.e., static differences between markets-and long-run effects-if these effects increase or decrease over time. Macroeconomic factors fluctuate over time in their impact on price dispersion. Microeconomic factors, mainly competition between stores and differences in category assortments between stores, have a substantial shortrun correlation and an increased effect over time. When we add interactions to the trend, our measure of price dispersion, we found that price dispersion is twice higher: 6.3%.
Keywords: D4; F40; L1; 330; Price Dispersion; Market Segmentation; Retail Industry